Selling difficulty: the case of Christine Brooke-Rose. Issue 2 (7th February 2018) - Pohl, Rebecca
ABSTRACT: The description of Christine Brooke-Rose's texts as 'difficult' is a pervasive rhetorical commonplace, habitually invoked in interviews, reviews and articles. Brooke-Rose herself contributed to this discourse of difficulty surrounding her work, remaining unapologetic about the demands her writing makes on readers, but also insisting on the pleasure of the text. In this article, I trace the complex relationship between difficulty, pleasure and sales that marks Brooke-Rose's writing career through her correspondence with publishers and her novel Textermination . Making extensive use of her archive, I investigate the ways in which difficulty is produced in the process of writing, in the text itself, and also the ways in which difficulty is negotiated in the course of publication. This paper argues that Brooke-Rose's writing troubles any easy opposition between pleasure and difficulty. This pivots on what I call the problematic of recognition central to Brooke-Rose's work – for the reader, in the text and of the writer. The paper is framed by an enquiry into the institutional writerly labour involved in securing literary reputation.